The essence of the main tasks of the Ukrainian cyber defense system - Zhivilo , E.O. (Theory and Practice of Public Administration, 2019)
The essence of modern directions of creation and functioning of the state cyber defense system is analyzed. A uniform approach has been developed in the Ministry of Defense of Ukraine, the Armed Forces of Ukraine and the State Special Transport Service of Ukraine regarding the implementation of measures for the preparation and conduct of the cyber defense. The theoretical bases of normative-legal support of activities in the field of cyber defense are substantiated. In the conditions of acquiring combat capabilities, components of the security and defense sector of the state are substantiated, and the creation of appropriate units of vulnerability detection and response to cyber incidents and cyber attacks on cyber defense objects in the above-mentioned structures has been grounded. The basic tasks of the cyber defense system of Ukraine are determined. Given the novelty of the concept of "cyber-defense", as well as the lack of a unified approach in the Ministry of Defense of Ukraine, the Armed Forces of Ukraine and the State Special Transport Service of Ukraine, the implementation of measures for the preparation and conduct of the cyber defense, the creation and operation of the cyber defense system should be considered in detail directions and tasks. In the future, the functioning of the cyber defense system of the state, in relation to the implementation of assignments, will directly depend on: - Main directions of activity of the Ministry of Defense of Ukraine, the Armed Forces of Ukraine and the State Special Transport Service of Ukraine; - acquisition and further development of the necessary and sufficient capabilities of the Ministry of Defense of Ukraine, the Armed Forces of Ukraine and the State Special Transport Service of Ukraine for effective action in the information (cybernetic) space and achievement of interoperability with NATO; - Practical implementation of current measures to respond to the enemy’s actions in cyberspace, preparation and conduct by the Armed Forces of Ukraine and the State Special Transport Service of Ukraine of the cyber defense in everyday activities, during preparation and application, including their participation in the operation of the Joint Forces, anti-terrorist operations.